A study of nanoparticle shape in water/alumina/boehmite nanofluid flow in the thermal management of a lithium-ion battery under the presence of phase-change materials - Jiang, Y. (Elsevier B.V., 2022)
The passive method of using phase-change materials (PCMs) and the active method of using forced nanofluid flow are employed to control the temperature of a battery pack. The battery pack is of the cylindrical lithium-ion (Li-ion) type and in the form of a cubic pack. The PCM used occupies the whole space in the cube. The nanofluid flows in a helical channel inside the battery pack. Water/alumina/boehmite was used as the nanofluid with different nanoparticle shapes. Parameters such as the temperature of the battery and the heat transfer coefficient (HTCO) were numerically studied by varying the nanofluid velocity. COMSOL software is used to simulate the battery pack and the nanofluid flow inside it. The major results indicated that the blade-shaped nanoparticles led to the largest drop in the maximum (MAX) temperature and the amount of molten PCM at different times compared to other nanoparticle shapes. Increasing the nanofluid velocity from 0.02 to 0.06 m/s reduced the amount of molten PCM by 4.7 and resulted in a 70 increase in HTCO nanofluid. In addition, this rise in velocity reduced the MAX and average (AVG) temperature of the battery by 1.24 °C and 1.53 °C, respectively, and decreased the outlet nanofluid temperature by 0.44 °C. © 2022 Elsevier B.V.